2018
DOI: 10.1021/acs.cgd.7b01717
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Fluoride on Octacalcium Phosphate and Apatite Formation on Amorphous Calcium Phosphate Substrate

Abstract: As fluoride is known to affect the biomineralization of calcium phosphates, we examined how the growth at 37 °C of octacalcium phosphate (OCP) and hydroxyapatite (HAp) on an amorphous calcium phosphate substrate is affected by low-dose fluoride (0–2 ppm) in metastable calcium phosphate solution. In the absence of fluoride, highly oriented plate-like OCP crystals grow on the substrate. With 0.7–0.8 ppm fluoride, OCP crystal formation was greatly modulated (the crystals were smaller and their orientation was low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 46 publications
2
43
0
1
Order By: Relevance
“…Although the present study did not directly demonstrate the presence of ACP in the outermost layer of enamel, its presence is suggested based on the findings that Mg ions are involved in the stability of ACP and that the Mg value was highest at the outermost layer of the Pr-E specimens. This finding is supported by the in-vitro study conducted by Iijima et al 26) , which showed the transformation of ACP to HAp via OCP.…”
Section: Formation Of Mg Present In the Interface Between Pre-eruptivsupporting
confidence: 68%
“…Although the present study did not directly demonstrate the presence of ACP in the outermost layer of enamel, its presence is suggested based on the findings that Mg ions are involved in the stability of ACP and that the Mg value was highest at the outermost layer of the Pr-E specimens. This finding is supported by the in-vitro study conducted by Iijima et al 26) , which showed the transformation of ACP to HAp via OCP.…”
Section: Formation Of Mg Present In the Interface Between Pre-eruptivsupporting
confidence: 68%
“…On the other hand, the low fluoride content of the BioMinF ® (in contrast to the high fluoride content of the utilized fluoride gel), allowed the penetration of BioMinF ® rich content of calcium and phosphate through the porous enamel sub-surface, causing the re-mineralization of the demineralized enamel lesion rather than remineralizing the outer enamel surface, as was observed when using fluoride as a sole remineralizing agent. Moreover, previous research showed that the presence of low concentration of fluoride in the BioMinF ® glass facilitated apatite formation, since fluorapatite forms at about a unit of pH lower than hydroxyapatite, and fluoride is known to catalyze the conversion of brushite, octacalcium phosphate, and amorphous calcium phosphate to apatite [ 27 ]; which may explain the decrease in the roughness of the BioMinF ® glass specimens’ SEM-EDS images, due to the repair action exerted by the BioMinF ® paste [ 13 , 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…reported that Mg ions suppressed the conversion of ACP to HAP. Iijima et al 29) . added fluoride to Ca and P ion solutions, and when the fluoride concentration was increased to 1 ppm or more, the nano-rod hydroxyapatite precipitated directly from the base of ACP plate without going through an OCP step.…”
Section: Continuous Crystal Change Of Calcium Phosphatementioning
confidence: 99%